Regulation of the proneural gene achaete by helix-loop-helix proteins. - Martínez, C (1993)
The Achaete (Ac) protein, a transcriptional regulator of the basic-helix-loop-helix (bHLH) type, confers upon ectodermal cells the ability to become neural precursors. Its temporally and spatially regulated expression, together with that of the related Scute (Sc) protein, helps define the pattern of Drosophila melanogaster sensory organs. We have examined the transcriptional control of the ac gene and shown, using in vivo assays, that several E-boxes, putative interacting sites for bHLH proteins, present in the ac promoter are most important for ac regulation. They most likely mediate ac self-stimulation and sc trans-activation. We also demonstrate that ac transcription is negatively regulated in vivo by the gene extramacrochaetae (emc) in a manner dependent on Ac and Sc products. emc encodes an HLH protein that lacks the basic region and presumably antagonizes Ac and Sc function by sequestering these proteins in complexes unable to interact with DNA. Our results strongly support the model of negative regulation of emc on ac and sc transcription through titration of their products. As currently thought, this seems accomplished by heterodimerization via the HLH domain, because an amino acid substitution in this region abolishes the emc antagonistic effect both in vitro and in vivo.